Ink-jetting-based conformal additive manufacturing: advantages, opportunities, and challenges - Hao Yi; Xiaoqi Guo; Fangle Chang; Huajun Cao; Jia An; Chee Kai Chua (International Journal of Extreme Manufacturing)
Ink-jetting printing stands out among various conformal additive manufacturing techniques for its multi-material, digital control, and process flexibility. Ink-jetting-based conformal additive manufacturing is renowned for its adaptability to complex topological surfaces and is emerging as a critical technology for future comprehensive conformal printing systems. This review highlights the distinctiveness of four primary ink-jetting printing techniques in conformal additive manufacturing—piezoelectric jetting, thermal bubble jetting, aerosol jetting, and electrohydrodynamic jetting—and delves into how these attributes endow ink-jetting printing with unique advantages in conformal processes. Furthermore, leveraging these advantages, the review discusses potential applications in conformal electronics, energy devices, biology, and electromagnetics to bolster the ongoing development and application. Considering the current state of this technology, the review identifies critical challenges for future advancements, such as dynamic surface printing, integrated fabrication of multifunctional conformal structures, and the balance between resolution and throughput. This review summarizes the latest research and technological advancements in ink-jetting-based conformal additive manufacturing, aiding in its innovative applications and enhanced manufacturing capabilities in the future.